A widower's lament : the Pious meditations of Johann Christoph Oelhafen - Oelhafen von Schöllenbach, Johann Christoph, 1574-1631 (Fortress Press, 2021)
This book deals with Christian lament in the late Reformation by exploring the efforts of a talented yet little-known layman to cope with the death of his beloved wife. It provides full access to the remarkable work of private devotion that he authored to express his lament. A work of haunting candor and searching faith, The Pious Meditations furnishes insight into life in the past as well as resources for life in the present.